Application of salivary antibody immunoassays for the detection of incident infections with Norwalk virus in a group of volunteers - Griffin, Shannon M. (J Immunol Methods, 2015)
Norovirus infection is the most common cause of acute gastroenteritis in developed countries. Developing an assay based on a non-invasive biomarker for detecting incident norovirus infections could improve disease surveillance and epidemiological investigations. This project involved analysis of IgA and IgG norovirus-specific antibody responses in saliva samples from a Norwalk virus (Genogroup I, genotype 1 norovirus) challenge study involving infected and symptomatic, and non-infected asymptomatic individuals. Saliva was collected at the challenge, and two weeks and 40 days post-challenge. Samples were analyzed using the Luminex fluorometric and Meso Scale Discovery (MSD) electrochemiluminescence immunoassays. Recombinant P domains of Norwalk virus capsid protein, as well as similar recombinant proteins of two genogroup II noroviruses (VA387 and VA207) were used as antigens. Immunoconversions were defined as >4-fold increase in antibody responses to the norovirus antigens. Various sample pre-treatment options, buffers, saliva dilution ratios, and data adjustment approaches to control for sample-to-sample variability in saliva composition were compared using the Luminex assay. The results suggest that adjusting responses to the norovirus antigens for responses to the protein purification tag, glutathione-S-transferase (GST), significantly improved the odds of producing a correct immunoconversion test result. IgG-based tests were more accurate compared to IgA-based tests. At optimal conditions, both Luminex and MSD assays for Norwalk-specific IgG antibodies correctly identified all infected and non-infected individuals. There was no evidence of cross-reactivity of anti-Norwalk virus antibodies with genogroup II noroviruses. These results suggest that salivary antibody responses can be used for the detection of incident infections with Norwalk virus in prospective surveys.